Interfaces da robótica educativa na ensinagem de alguns elementos de geometria plana no ensino fundamental - Provin, Sara (2020)
Recently, basic education has gone through a period of curricular restructuring, aiming to contemplate the guidelines proposed by the National Common Curricular Base (BNCC). The Mathematical curriculum component highlights the association of students' empirical knowledge with situations in which relationships with its contents can be established through tables, figures and schemes, seeking, as far as possible, to include the use of digital technologies. In the thematic unit Geometry, some basic elements such as straight, semi-straight, parallel lines, perpendicular lines, angles and flat figures such as triangles and quadrilaterals, are some objects of knowledge proposed by BNCC for the 6th and 7th grades of Elementary School. Unit that can be benefited by the educational robotics interfaces. In this context, this dissertation is part of the research line “Information, communication and interaction technologies applied to the teaching of Sciences and Mathematics” and it is based on Seymour Papert's Construction Theory, according to which the apprentice conceives his knowledge when manipulating and interacting with his object of study, as well as on the concept of teaching processes by Léa das Graças Camargos Anastasiou, according to which the teacher and the student are active subjects involved in the search for knowledge. In this context, a didactic sequence was developed to approach some basic notions of plane geometry, foreseen for the 6th and 7th grades. This was structured in 13 meetings and it was developed with a group of students from the Educational Robotics Project in the municipality of Erechim-RS. The guiding question of this study was: how can educational robotics help the process of teaching some basic elements of flat geometry with elementary school students? The research, of a qualitative and participatory nature, focuses on analyzing the educational potential of a didactic sequence that uses educational robotics interfaces in the process of teaching some basic elements of flat geometry with elementary school students. As instruments for data collection, logbooks prepared by the teacher/researcher, artifacts elaborated by the students (such as robotics prototypes and their programming), photographic records and videos recorded during the application of the educational product were used. From the results obtained, it can be inferred that the proposal is valid and the use of educational robotics is recommended in the teaching of some elements of plane geometry. It was possible to observe in the practical activities, in answers presented during the questions and in the reports of the groups, the relationship between what they had researched and what was reproduced in the programming software and with the pre-programmed cart, confirming the relationship of geometric elements, through their active interaction between students and the object of study. Finally, it is emphasized that this dissertation is accompanied by an educational product that gathers the material used in the meetings and the didactic sequence developed, which is available at the address <http://<http://educapes.capes.gov.br/handle/capes/569464>.